Homoeopathic Approach to Managing Primary Infertility with Endometriosis: A Case Report (Homoeopathy for All, 2025)
Background: Primary infertility is  the inability of a couple to conceive  after at least one year of regular,  unprotected intercourse, with no  prior pregnancies. Endometriosis  is a leading cause of infertility. Endometriosis is the occurrence  of ectopic benign endometrial  tissue outside the cavity of the  uterus. Several theories have  been propounded to explain  endometriosis; with retrograde  menstruation is the most suitable  explanation for the development of  this disease. Mainly presented with  dysmenorrhea, dyspareunia and  infertility due to adhesions (blocking  the fallopian tubes), hormonal  distrubances. While conventional  management often involves surgical  interventions to remove adhesions.  Recurrence is not uncommon. Objectives: The objective of this  case report is to document the  clinical outcome of individualised  homoeopathic management in a  patient with primary infertility due  to endometriosis and to evaluate its  therapeutic potential as an alternative  in gynaecological disorders. Method: a 31-year-old female  presented with primary infertility  for 5 years. Diagnosed clinically as  primary infertility and endometriosis.  The case was analysed in detail,  and individualised homoeopathic  treatment was prescribed based on the  totality of symptoms. Lycopodium  clavatum in fifty-millesimal (LM)  scale was administered, starting  from 0/1 to 0/6 over a period of  three months. Clinical progress was  monitored regularly, and treatment  outcomes were assessed through  symptom resolution and ultrasound  sonography (USG).  Result: The patient showed  significant improvement and she  conceived after three months of  treatment. Photographic evidence  of USG documented the clinical  progress. The high total score (+8) on  the MONARCH scale established a  possible causal relationship between  the homoeopathic intervention and  the patient’s clinical improvement.  Conclusion: In this case,  individualised homoeopathic  treatment with Lycopodium  clavatum was effective in managing  endometriosis related infertility  within a plausible time frame. Further documentation and studies  are warranted to substantiate these  findings in the future.
Keywords: Endometriosis; Infertility; Fifty-millesimal; Homoeopathy; Lycopodium clavatum